2012
DOI: 10.1002/pssa.201127327
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrical properties in the K1/2Bi1/2TiO3–K1/2Bi1/2ZrO3 solid solution (KBT–KBZ)

Abstract: The present work is devoted to the study of the Zr4+/Ti4 substitution in the K1/2Bi1/2Ti(1–x)ZrxO3 solid solution (x = 0.0 to x = 1.0), based upon the K1/2Bi1/2TiO3 (KBT) ferroelectric compound. The tetragonal distortion of KBT is suppressed by this substitution and leads to the cubic compound K1/2Bi1/2ZrO3 (KBZ). These results agree with the values of the ionic radii of the Zr4+ and Ti4 ions ($r_{{\rm Ti}^{4 + } } $ = 0.605 Å and $r_{{\rm Zr}^{4 + } } $ = 0.72 Å). Close to KBT (x ≤ 0.05), the symmetry remains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
25
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 60 publications
8
25
0
Order By: Relevance
“…Interestingly, the refinement for KBT (x = 0) by Bengagi et al shows the (111) reflection to be significantly undercalculated. 16 A better fit to the peak profile was obtained here by refining for strain factors. The improvement is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the refinement for KBT (x = 0) by Bengagi et al shows the (111) reflection to be significantly undercalculated. 16 A better fit to the peak profile was obtained here by refining for strain factors. The improvement is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These systematic trends suggest that Ti/Zr atoms are randomly distributed in the lattice, 13,14 with no significant clustering. The local crystal structure from x = 0.5 to 0.9 ( previously reported as cubic 16 ) does not appear to ever become completely centrosymmetric, with Ti remaining off-centered. This is consistent with our high-resolution SXRD diffraction results, and the observation of weak ferroelectricity up to x = 0.9 by Bengagi et al 16 Fig.…”
Section: Xanesmentioning
confidence: 92%
See 1 more Smart Citation
“…If a heat-treated sample includes two perovskite phases with different Zr/Ti ratios as reported for the solid-state synthesis, a strong split of the (111) peak in its XRD pattern should be observed. 18) However, none of the (111) peaks for the various compositions are split. Moreover, with increasing Zr content, these peaks obviously shift toward lower angles, as observed in the case of the as-synthesized samples; accordingly, the unit-cell volume monotonically increases, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bengagi et al attempted to fabricate Zr-substituted BKT [i.e., (Bi 1/2 K 1/2 )-(Zr x Ti 1¹x )O 3 , denoted as BKZT hereafter] ceramics via a conventional solid-state reaction and found that the products included two perovskite phases with different Zr/Ti ratios even after extended thermal annealing as long as 100 h. 18) In another study, Liu et al reported the preparation of single-phase BKZT powders via a solid-state reaction involving a similar long calcination time. 19) However, in their case, a large excess of K 2 CO 3 was added to the samples to compensate for the evaporation of K 2 O during the prolonged calcination.…”
Section: Introductionmentioning
confidence: 99%